Pocket Echocardiography System for Detection of Patent Ductus Arteriosus in Neonates. Issue 2 (11th June 2014) - Torrazza, Roberto Murgas; Chandran, Arun; Co‐Vu, Jennifer; DeGroff, Curt
<x xml:space="preserve">Abstract</x> Background Neonates are commonly referred for a cardiology consult and an echocardiogram to rule out patent ductus arteriosus (PDA). Objectives Evaluate the usefulness of current pocket echocardiography system (PES) in PDA detection compared to traditional full‐featured echo system (FFES). Hypothesis The determination of the presence of a PDA in neonates can be done using PES. Methods Fifty newborns with orders for echo evaluation were included in this study. A 5‐minute PES scan was performed first. Then a full echo study was performed on a traditional FFES. Images were evaluated by three pediatric cardiologists blinded to the patients and the FFES results. Results The overall accuracy of reviewers rating PES versus FFES to rule in PDA had low false‐positive rates 9.5% (95% CI: 1.2–30%), 11.8% (95% CI: 1.5–36%), 11.1% (95% CI: 1.4–35%) and the false‐negative rate to rule out PDA was 0% (95% CI: 0–18%), 5.5% (95% CI: 0.14–27%), 0% (95% CI: 0–26%) for each reviewer 1, 2, and 3, respectively. Upon further analysis, PES scan was shown not to be accurate on infants with body weight below 1000 g with encouraging results for infants above 1000 g and those >37 weeks gestational age. Conclusions Our results suggest that the current PES could potentially be used in larger and near‐term infants but has less than acceptable performance in low birth weight and premature infants in determining who should undergo a FFES study for persistent PDA diagnosis. Improvements in the technology along with developing limited training protocols for noncardiology personnel should make it possible for PES scan to be used as a screening tool and as an extension of physical examination especially in limited resource settings.